Thermal Hydrolysis of Urea for On-site Generation of Ammonia and Carbon Dioxide (Chemical Engineering Research Bulletin, 2023)
Thermal hydrolysis of urea into ammonia and carbon dioxide gases via ammonium carbamate is an accepted method for recovery of ammonia and carbon dioxide from dilute urea solutions in the urea production process as well as for removal of urea from the process wastewater. On-site generation of ammonia from urea by hydrolysis by the utilities to control NOx emission has proven to be a safe and reliable alternative to either anhydrous or aqueous ammonia, which is subject to strict OSHA and EPA regulations for transport, storage and handling. An experimental investigation was undertaken to study the thermal hydrolysis of urea for on-site generation of ammonia and carbon dioxide for local small users. Aqueous solutions of urea (1-5% w/w) were hydrolyzed in an electrically heated hydrolyzer set-up at pressures ranging from atmospheric to 5 kg/cm2g with conversion of 1.18 to 44% of the urea fed to ammonia and carbon dioxide. The extent of hydrolysis was determined by measuring the urea concentration of the solution at the end of each experiment by colorimetric P-Dimethyl-aminobenzaldehyde method that is used by the local ammonia-urea industry. The hydrolysis was pressure dependent, and it was the lowest at atmospheric pressure. The conversions in terms of percent urea hydrolyzed were higher with lower urea concentrations. It was also observed that the pHs of the hydrolyzed solutions were more than those of original urea solutions. And the unit for on-site hydrolysis of urea to obtain ammonia and carbon dioxide would not be one-step simple process in reality.Chemical Engineering Research Bulletin 23(2023): 6-9